2010
DOI: 10.1371/journal.pone.0011880
|View full text |Cite|
|
Sign up to set email alerts
|

An Open-Label, Randomised Study of Dihydroartemisinin-Piperaquine Versus Artesunate-Mefloquine for Falciparum Malaria in Asia

Abstract: BackgroundThe artemisinin-based combination treatment (ACT) of dihydroartemisinin (DHA) and piperaquine (PQP) is a promising novel anti-malarial drug effective against multi-drug resistant falciparum malaria. The aim of this study was to show non-inferiority of DHA/PQP vs. artesunate-mefloquine (AS+MQ) in Asia.Methods and FindingsThis was an open-label, randomised, non-inferiority, 63-day follow-up study conducted in Thailand, Laos and India. Patients aged 3 months to 65 years with Plasmodium falciparum mono-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 37 publications
6
86
2
1
Order By: Relevance
“…For the ITT population, PCR-corrected cure rates were 87.9% for DHA-PQP and 86.6% for AS-MQ. As expected, better absolute but comparatively similar results were obtained for the per protocol population with PCR-corrected cure rates of 98.7% for DHA-PQP and 97.0% for AS-MQ (Valecha et al, 2010). Comparison of the data of this study to data from other country found no differences between the primary outcome measures, further confirming that DHA-PQP was similarly active against the P. falciparum found in India, Laos and Thailand, relative to AS-MQ.…”
Section: -Day In Vivo Protocol To Test Acts Efficacysupporting
confidence: 82%
See 3 more Smart Citations
“…For the ITT population, PCR-corrected cure rates were 87.9% for DHA-PQP and 86.6% for AS-MQ. As expected, better absolute but comparatively similar results were obtained for the per protocol population with PCR-corrected cure rates of 98.7% for DHA-PQP and 97.0% for AS-MQ (Valecha et al, 2010). Comparison of the data of this study to data from other country found no differences between the primary outcome measures, further confirming that DHA-PQP was similarly active against the P. falciparum found in India, Laos and Thailand, relative to AS-MQ.…”
Section: -Day In Vivo Protocol To Test Acts Efficacysupporting
confidence: 82%
“…The 28-day follow-up protocol (Chanda et al, 2006;Denis et al, 2002;Marquino et al, 2003) or 42-day follow-up protocol (Leang et al, 2015;Mårtensson et al, 2005;Mayxay et al, 2004;Valecha et al, 2010;Yeka et al, 2008) were usually used. Few studies used 63-day follow-up protocols for efficacy monitoring of ACTs containing a long half-life partner drug (Sodiomon et al, 2016;Valecha et al, 2010). Patient follow-ups were scheduled for days 1, 2, 3, 7, 14, 21 and 28 plus any other day that the child was taken to the clinic on an unscheduled day.…”
Section: In Vivo Act Efficacy Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel combination currently introduced into the ACT portfolio is dihydroartemisinin-piperaquine, which performs well compared to the ACTs in current use [12][13][14].…”
Section: New Drugs: Dihydroartemisinin-piperaquine and Fosmidomycinmentioning
confidence: 99%